O Supremo Tribunal Federal e o discurso de ódio nas redes sociais: Exercício de direito versus limites à liberdade de expressão - Napolitano, Carlo José [UNESP]; Stroppa, Tatiana (Centro de Ensino Unificado de Brasilia, 2017)
This text is part of ongoing research that investigates Brazilian Supreme Court decisions related to the public policies communications, especially those that deal with the freedom of speech. This paper, supported by bibliographical and documental research, specifically aims to analyze STF decisions related to hate speech in social media, concluding that the hate speech theme has not yet entered in the agenda of the Brazilian Supreme Court, which is one of the limitations of this research, as well is indicated faults in the processes indexing in the STF site, which makes it difficult to carry out researches, pointing out the necessity to improve the indexation of the STF's research terms. For these reasons, this is an innovative article related to STF researches.
The Brazilian Supreme Court and the hate speech in social media: Rights exercise versus freedom of speech limits
Keywords: Brazilian Supreme Court; Hate speech; Social media